2018
DOI: 10.1111/jicd.12341
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorders among a cohort of university undergraduates in Australia

Abstract: The overall prevalence of TMD symptoms in the population studied was 77.2%, with female preponderance of TMD symptoms (83%). This is higher than the estimated prevalence (23%) in the Australian general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
3
3
1
4
Order By: Relevance
“…In addition, the prevalence of TMJ sounds, in this study, was increased according to the severity of TMD. These findings are consistent with those of other studies 15,18,30 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, the prevalence of TMJ sounds, in this study, was increased according to the severity of TMD. These findings are consistent with those of other studies 15,18,30 .…”
Section: Discussionsupporting
confidence: 94%
“…Based on the epidemiological studies, a broad prevalence peak of TMD symptoms is present between 20 and 40 years of age, with a lower prevalence in younger and older people [11][12] . Many studies published related to the unıversity students of different countries have reported that the TMD prevalence ranged from 17% to 87% due to differences in the populations studied, diagnostic criteria, examination methods, and inter-and/or intra-rated variations of examining practitioners [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Resultsmentioning
confidence: 99%
“…O estudo de Joury 9 neste aspecto foi dissonante, não encontrando associação entre sexo e a prevalência da DTM. Lung et al 13 também não identificaram, em estudantes universitários, diferença estatística da DTM entre gêneros. Entretanto vale ressaltar os diferentes critérios de classificação das DTM nesses estudos.…”
Section: Discussionunclassified
“…No presente estudo verificou-se alta prevalência de sintomas de DTM na população acadêmica, sendo a maioria de grau leve, o que corrobora estudos que também utilizaram o mesmo instrumento de pesquisa [13][14][15][16] , bem como outros instrumentos 21. Quanto aos sintomas mais relatados, ruídos (cliques e estalos) nas articulações também foram prevalentes em outros estudos, os quais observaram prevalência de 31,9% a 48,5% na população estudada [13][14]21 .…”
Section: Discussionunclassified
“…A literatura aponta que as mulheres relatam mais sintomas de DTM do que os homens. 21 Outra sugestão seria abordar outros cursos de outras áreas do conhecimento e também cursos que sejam oferecidos no período diurno, a fim de investigar se há relação entre área do conhecimento ou período diário da oferta do curso com as demais variáveis pesquisadas.…”
Section: Discussionunclassified